Hydrogen Evolution Reaction: Synergistically Tuning Water and Hydrogen Binding Abilities Over Co4N by Cr Doping for Exceptional Alkaline Hydrogen Evolution Electrocatalysis (Adv. Energy Mater. 41/2019). Issue 41 (6th November 2019) - Yao, Na; Li, Peng; Zhou, Zirui; Zhao, Yuanmeng; Cheng, Gongzhen; Chen, Shengli; Luo, Wei
Abstract : In article number 1902449, Shengli Chen, Wei Luo, and co‐workers report a general approach for boosting the alkaline hydrogen evolution reaction performance of Co4 N though synergistically tuning the water and hydrogen binding abilities by Cr doping, resulting in a low overpotential of 21 mV to achieve the current density of 10 mA cm −2 and long‐term stability in alkaline media.